The juxtaposition of apostasy & absolute rights of freedom of religion: the quandary of apostate - Shariffuddin, Norashikin; Abang Bolhil, Abang Ikhbal; Zulkifli, Norsyazrah; Dato Syed Hamid, Sharifah Shatrah (2023)
Article 11 of the Federal Constitution of Malaysia grants everyone the right to profess and practice his religion. However, Article 11(4) stipulates that federal law may control or restrict the propagation of any religious doctrine or belief among those who practice Islam. Past studies have identified that freedom of religion exists in Malaysia but not absolute. Nonetheless, there is a lack of research on safeguarding the freedom of religion pertaining to the issue of apostasy. This paper aims to explore the scope of freedom of religion pertinent to apostasy. This study employed doctrinal qualitative research using both primary and secondary data such as legislation, cases, articles, and other relevant documents. Researchers found that Malaysia should establish a clear legal framework to settle the issue of apostasy as the freedom of religion is not absolute as it appears. This study is also significant in aiding the legislators to review and revise the law accordingly and thus, will correspond to meet the needs of the citizens of Malaysia especially on the right to apostate.